(untitled) - Talaro, Kathleen Park (Boston, 2005)
Written with the non-major/allied health student in mind, the authors use common, everyday analogies to explain the many difficult microbiology concepts. Unlike any other allied health microbiology textbook on the market, the art program showcases beautiful illustrations with the use of bold, primary colors. This version of Foundations in Microbiology includes chapters 1 through 17 of the full text, teaching only the basic principles of microbiology and not covering the clinical aspects.
Keywords: Medical microbiology,Microbiology,Vi sinh học,Vi sinh học y tế